Smart computing and communication : 4th International Conference, SmartCom 2019, Birmingham, UK, October 11-13, 2019, Proceedings /: 4th International Conference, SmartCom 2019, Birmingham, UK, October 11-13, 2019, Proceedings. (2019) - Unknown
No abstract available